Performance Improvement through Implementation of Lean Maintenance - Kolanjiappan, S; Maran, K (Journal of Commerce and Trade, 2011)
Lean Maintenance is a relatively new term, invented in the last decade of the twentieth century, but the principles are well established in Total Productive Maintenance (TPM). Lean Maintenance—taking its lead from Lean Manufacturing—applies some new techniques to TPM concepts to render a more structured implementation path. Tracing its roots back to Henry Ford with modern refinements born in Japanese manufacturing, specifically the Toyota Production System (TPS). Lean seeks to eliminate all forms of waste in the manufacturing process—including waste in the maintenance operation. Plants can accelerate their improvements with much lower risk through the elimination of the defects that create work and impede production efficiency. Optimizing the maintenance function first will both increase maintenance time available to do further improvements and will reduce the defects that cause production downtime. Thus cost reduction and improved production are immediate results from establishing Lean maintenance operations as the first step in the overall Lean Enterprise transformation. This paper discusses the application of lean principles in maintenance of aircraft, and describes some of the lean tools and techniques that are being used to transform maintenance process. This research study was based upon defects occurred on ten aircrafts for the period of three years in one of the private aviation industry. System wise defects data were collected and the effect of the trend of these effects was investigated thoroughly.